DEPRESI, PENYEBAB DAN GEJALA DEPRESI - Indah Rizki Ramadani; Tryana Fauziyah; Bima Khoirur Rozzaq (LPPM Politeknik Pratama, 2024)
ThisThis research aims to determine the definition, causes and symptoms of depression. Semiotic research and approach is a method that examines and analyzes signs or symbols in a cultural or social context. Semiotics itself is the study of signs and their meaning. This approach views signs ascommunication media that create meaning in a society. This research examines the film